Post-Transplant Management of Nonimmunologic Complications: A Brief Overview - Radovančević, Branislav (1987)
Cardiac transplantation has become such a well-accepted mode of treatment for end-stage heart disease that during the last several years the procedure has been performed at centers that lack fully specialized staff and facilities. Most complications occurring in heart-transplant recipients are related to rejection and infection, but other complications can also cause increased morbidity and mortality. These include hemorrhage and non-rejection-related heart failure, dysfunction of other organs, and psychological and nutritional problems. In this overview, I emphasize that every problem regarding heart transplant recipients requires a planned response that results in immediate treatment, and I provide information on protocols and procedures in use at the Texas Heart Institute, where over 200 cardiac-transplantation procedures have been performed since 1982. (Texas Heart Institute Journal 1987; 14:252-256)